2020
DOI: 10.1002/jbm.b.34640
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of gum‐based composite scaffolds for enhanced strength and stability: A comparative study between sodium trimetaphosphate and glutaraldehyde

Abstract: Tissue engineering is one of the potential fields in the domain of regenerative medicine. Engineered scaffolds are an excellent substitute for the conventional use of bone grafts as they are biocompatible, economic, and provide limitless supply with no risk of disease transmission. Gum-based scaffolds present a good scope for studying tissue-engineering models and analyzing controlled drug delivery. Uniform blending of the gums and the presence of the optimal concentration of appropriate crosslinkers are very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Among them, glutaraldehyde, for sure, is most often described; it is broadly used as a crosslinking agent for several biopolymers. Among them, chitosan [ 38 ] sodium alginate [ 39 ], cellulose [ 40 ], or gellan gum [ 41 ] can be distinguished. For example, polymer microspheres can be prepared by mixing solutions of polymer and glutaraldehyde in a mixture of oil and surfactants.…”
Section: Other Methods Of Gelationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, glutaraldehyde, for sure, is most often described; it is broadly used as a crosslinking agent for several biopolymers. Among them, chitosan [ 38 ] sodium alginate [ 39 ], cellulose [ 40 ], or gellan gum [ 41 ] can be distinguished. For example, polymer microspheres can be prepared by mixing solutions of polymer and glutaraldehyde in a mixture of oil and surfactants.…”
Section: Other Methods Of Gelationmentioning
confidence: 99%
“…It turned out that crosslinking with GA resulted in lower degradation rates. According to the mechanical strength resistance toward the compressive forces, STMP-modified materials revealed better properties than GA. Additionally, the cell viability experiments showed that STMP can be regarded as a safer crosslinking agent [ 41 ].…”
Section: Chemical Crosslinking: Mechanisms and Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPL composite hydrogels formed a layered structure in comparison to the pristine NPN films with smooth surfaces. STMP crosslinked with PEDOT:PSS to form a scaffold structure [61] at high concentration, as indicated by NPH and LPH (Figure 2E,F). For the LPH group, adding glycerol to STMP-based PEDOT:PSS hydrogels resulted in no significant morphological changes (Figure 2F).…”
Section: Hydrogel Morphologymentioning
confidence: 98%
“…5,6 Gellan gum-based hydrogels or composite scaffolds have been applied for intervertebral disc and skeletal muscle tissue engineering, the dispersion of neural stem/progenitor cells (NSPCs), peripheral nerve regeneration, the promotion of fibroblast differentiation, skin wound healing, bone and cartilage tissue engineering and potential osteogenesis. [7][8][9][10][11][12][13][14] Hence, gellan gum is a promising candidate for applications in the field of tissue engineering of human tissues, such as skin.…”
Section: Introductionmentioning
confidence: 99%